The Lower Tagus Valley (Portugal) earthquakes: Lisbon 26 January 1531 and Benavente 23 April 1909 - Teves-Costa, Paula; Batlló, Josep; Cabral, João (Física de la Tierra, 2017)
The Lower Tagus Valley (LTV) has been the source of several local earthquakes that affected the region of Lisbon, in the central part of Portugal. In spite of absence of strong earthquakes during the last 100 years, past events have produced large damage in this area. We present the state of the art concerning the last two major earthquakes, which occurred in 1531 and 1909. The effects of both events are described, based on coeval reports already interpreted by several authors. The source parameters determined by different authors are also presented. The characterization of the seismogenic potential of the LTV is very important to better estimate the seismic hazard and risk of the region of Lisbon and Tagus Valley.
Keywords: Lower Tagus Valley; 1531 Lisbon earthquake; 1909 Benavente earthquake; historical earthquakes.